ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI IMPOR CENGKIH INDONESIA - Almanico Islamy Hasibuan; Yusman Syaukat; A. Faroby Falatehan (JRB-Jurnal Riset Bisnis, 2022)
ABSTRACTOne of plantation commodities that has potential to become a source of foreign exchange for Indonesia is cloves (Syzigium aromaticum L. Marr. and Perr.). National cloves production fluctuates, so that in cloves production it is known as the big, medium, and small harvest. The clove cigarette industry is the main consumer because it absorbs 95% of the national clove production which is used as the main raw material in producing. This causes the volume of cloves to exported reduced. Apart from being a clove exporting country, Indonesia also imports. Cloves used in this study are cloves with the (HS) code 0907 (Whole fruit, cloves, and stems). Indonesia imports cloves to meet domestic demand, especially from the cigarette industry. Appropriate government policies related to cloves import are important, so that supply of cloves in both domestic and world markets is met. Therefore, this study aims to analyze the development of Indonesia's clove and trade policy and its implications for volume and value of clove imports. Key words: Cloves import, cloves import policy, Cochrane-Orcutt method, Ordinary Least Squares (OLS). ABSTRAKSalah satu komoditas perkebunan yang berpotensi menjadi sumber devisa Indonesia adalah cengkih (Syzigium aromaticum L. Marr. and Perr.). Produksi cengkih nasional sering mengalami fluktuasi, sehingga dikenal panen raya, panen sedang, dan panen kecil. Industri rokok kretek merupakan konsumen utama cengkih karena menyerap 95% produksi cengkih nasional yang digunakan sebagai bahan baku utama dalam berproduksi. Selain sebagai negara pengekspor cengkih, Indonesia juga melakukan impor cengkih. Cengkih dalam penelitian ini menggunakan cengkih dengan kode (HS) 0907(Whole fruit, cloves, and stems). Indonesia melakukan impor cengkih untuk memenuhi permintaan domestik. Kebijakan pemerintah yang tepat terkait impor cengkih sangat penting agar persediaan cengkih baik di pasar domestik maupun pasar dunia terpenuhi. Oleh karena itu, penelitian ini bertujuan untuk menganalisis perkembangan cengkih dan kebijakan impor cengkih Indonesia dan implikasinya terhadap volume dan nilai impor cengkih. Kata kunci: Impor cengkih, kebijakan impor cengkih, metode Cochrane-Orcutt, Ordinary Least Squares (OLS).